Analisis Kualitas Pelayanan dan Fasilitas Ruang Tunggu Terhadap Kepuasan Penumpang di Bandara - Muzayyin, Akmal; Attabi, Naufal M.; Kalbuana, Nawang (Lembaga Intelektual Muda (LIM) Maluku, 2025)
The purpose of this article is to build hypotheses of influence between variables and present a comprehensive synthesis of previous research on factors that influence passenger satisfaction, particularly service quality and waiting room facilities at airports. The method used is a qualitative literature review by analyzing ten relevant national and international journals. Data were collected through searching scientific journal databases using appropriate keywords, then selected based on eligibility criteria such as topic relevance, year of publication, and publication quality. Data analysis was conducted using thematic synthesis techniques, which grouped previous research findings into main themes, compared results between studies, and identified patterns of relationships between variables. The results showed that service quality has a positive and significant effect on passenger satisfaction, waiting room facilities have a positive and significant effect on passenger satisfaction, and the two factors simultaneously have a positive and significant effect on passenger satisfaction. These findings confirm that service quality and waiting room facilities are the main pillars in creating passenger satisfaction, so airport managers need to continue to improve and evaluate these two aspects on an ongoing basis